EDUKASI ANEMIA SEBAGAI PENCEGAHAN PRIMER STUNTING PADA REMAJA PUTRI DI KELURAHAN PASIE NAN TIGO KECAMATAN KOTO TANGAH KOTA PADANG - Meri Neherta; Lili Fajria; Ira Mulya Sari; Yelly Herien; Novita Sari; Sri Wahyuningsih; Safiyah Kamilah; Mutia Rezky; Rini Anggraini (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Anemia in adolescent girls is very dangerous for both the short and long term. If it happens in the long term, after becoming a mother it will be detrimental to the baby in the future. Babies of anemic mothers will tend to give birth to premature babies later in the productive period of the teenager. Babies born to anemic adolescents are very at risk for malnutrition, then stunting. The purpose of this health education is to prevent anemia in adolescent girls as the primary prevention of stunting in toddlers. The implementation of this activity is carried out through 4 stages: situation analysis, preparation of needs for implementation of activities and evaluation of activities. The health education activities on anemia prevention were attended by 50 young women with pale conjunctiva criteria and often felt dizzy. The measuring instrument used is a questionnaire. The results of this activity in general can increase the knowledge of young women about anemia by 76%. Good knowledge before the activity was only 20%, after the activity increased to 96%. While the knowledge that is lacking before the activity is 80%, after the activity it is only 4%. Health education given to young women can increase knowledge in young women. It is hoped that young women can always eat balanced meals and blood-boosting tablets and disseminate this information to other young women. To the local health center to provide education on a regular basis every time they carry out youth posyandu activities.